(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This academic article discusses modernization and innovative strategies in teaching English, including the use of technology, learner-centered approaches, and experiential learning. It explores how these strategies can meet the changing needs of learners and create a more engaging and effective learning environment. The article provides valuable insights for French language teachers who want to improve their teaching practices and stay up-to-date with the latest trends in French language teaching.